Pengembangan bahan ajar teks fiksi berbasis kearifan lokal dalam pembelajaran literasi membaca peserta didik kelas IV sekolah dasar - Handayani, Tuwuh; Hendratno, Hendratno; Indarti, Titik (Universitas Lampung, 2022)
AbstractThis research aims to produce teaching materials for fiction texts based on local wisdom in reading literacy learning for fourth grade elementary school students that are valid, practical, and efficient on the theme My Living Area. This development research refers to the 4D Thiagarajan model. The research subjects were fourth grade students at SD Negeri Ngasem I, SD Negeri Ngasem III, and SD Negeri Sendangharjo, Bojonegoro Regency. The limited testing was carried out on 7 students and the broad testing was carried out on 35 students. Validation, observation, questionnaires, and tests are used as data collection techniques. The results of the research are 1) validity of teaching materials is proven from the aspect of material feasibility is 97%, language feasibility is 91%, presentation feasibility is 94%, and graphic feasibility is 93%, 2) the practicality of teaching materials is proven from the implementation of learning in the limited testing is 94% and the average in the broad testing is 94%, the activeness of students in the limited testing is 86% and in the broad testing the average is 89% is the very active category, the students who give a positive response in the limited testing and the broad testing are 98%, and 100% of teachers gave a positive response to the limited testing and the broad testing, 3) the effectiveness of teaching materials is proven from results of in the limited testing, the t-count value = 17,82 > t-table (2,447), while in the broad testing, the value of t-count = 37,448> t-table (2,042), based on the results of the t-test it is concluded that there is a significant difference between the results of the pretest and postest. Based on the results of this research, it can be concluded that the teaching materials of fiction texts based on local wisdom are valid, practical, and effective in reading literacy learning for fourth grade elementary school students. Keywords: teaching materials, fiction text, local wisdom, literacy learning